Broker-based service-oriented content adaptation framework - Md Fudzee, Mohd Farhan (2011)
Electronic documents are becoming increasingly rich in content and varied in format and structure. At the same time, user preferences vary towards the contents and their devices are getting increasingly varied in capabilities. This mismatch between rich contents and user preferences along with the end device capability presents a challenge in providing ubiquitous access to these contents. Content adaptation is primarily used to bridge the mismatch by providing users with contents that is tailored to the given contexts e.g., device capability, preferences, or network bandwidth. Existing content adaptation systems employing these approaches such as client-side, server-side or proxy-side adaptation, operate in isolation, often encounter limited adaptation functionality, get overload if too many concurrent users and open to single point of failure, thus limiting the scope and scale of their services. To move beyond these shortcomings, this thesis establishes the basis for developing content adaptation solutions that are efficient and scalable. It presents a framework to enable content adaptation to be consumed as Web services provided by third-party service providers, which is termed as “service-oriented content adaptation”. Towards this perspective, this thesis addresses five key issues – how to enable content adaptation as services (serviceoriented framework); how to locate services in the network (service discovery protocol); how to select best possible services (path determination); how to provide quality assurance (service level agreement (SLA) framework); and how to negotiate quality of service (QoS negotiation). Specifically, we have: (i) identified the key research challenges for service-oriented content adaptation, along with a systematic understanding of the content adaptation research spectrum, captured in a taxonomy of content adaptation systems; (ii) developed an architectural framework that provides the basis for enabling content adaptation as Web services, providing the facilities to serve clients’ content adaptation requests through the client-side brokering; (iii) developed a service discovery protocol, by taking into account the searching space, searching time, match type of the services and physical location of the service providers; (iv) developed a mechanism to choose the best possible combination of services to serve a given content adaptation request, considering QoS levels offered; (v) developed an architectural framework that provides the basis for managing quality through the conceptualization of service level agreement; and (vi) introduced a strategy for QoS negotiation between multiple brokers and service providers, by taking into account the incoming requests and server utilization and, thus requiring the basis of determining serving priority and negotiating new QoS levels. The performance of the proposed solutions are compared with other competitive solutions and shown to be substantially better.